PEDAGOGI KRITIS PAULO FREIRE DAN TRANSFORMASI POLITIK DI INDONESIA - Eka Januar Eka; Syamsul Rijal; Firdaus M Yunus; Suraiya IT (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2026)
This study analyzes the relevance of Paulo Freire's thoughts on critical education in the context of political transformation in Indonesia. Paulo Freire emphasizes the importance of dialogue, critical consciousness, and praxis as the main foundations in the process of human emancipation. In Freire's view, education serves not only as a transfer of knowledge, but also as a means of liberation to form a conscious, critical, and social-politically active subject. Indonesia as a developing democracy faces various political challenges, such as social polarization, low political literacy, and inequality of access and participation of citizens in the democratic process. This study uses a qualitative approach by analyzing secondary data in the form of books, scientific journals, and articles related to critical education and political dynamics in Indonesia. The analysis is focused on the potential application of Freire's thinking in answering the challenge of democracy. The results show that Freire-style critical education is relevant to encourage more inclusive, reflective, and democratic political participation. Critical education is able to equip citizens with critical thinking skills, awareness of political rights and obligations, and encourage active involvement in democratic life. Therefore, this study recommends the integration of Freire's critical education principles into the national education curriculum in order to strengthen the quality of democracy and encourage a more just and sustainable political transformation.